Mental Disorders in Patients during the Recovery Period after Viral Pneumonia Caused by COVID-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The SARS-CoV-2 virus can penetrate and infect the brain, but the mechanisms of the disease are not fully understood. It is unclear to what extent the severe neurological and psychiatric complications are due to a catastrophic overreaction of the immune system to the virus, known as hypercytokinemia; in what cases these complications may be due to a disproportionate thrombotic reaction; and whether concerns that some complications may be a consequence of massive empirical drug therapy are justified. It is unclear whether this damage is caused by an overreaction of the immune system, by medications, or by the virus itself. Understanding this is critical because these scenarios require very different therapeutic approaches and treatment regimens.